Conectando a cocriação de valor ao empreendedorismo digital: uma abordagem teórica e empírica em organizações - Poel, Naiche Van Der (2025)
Value co-creation can be understood as a collaborative process of creating value between organizations and their stakeholders, combining efforts, knowledge, resources, experiences and interests between them, and generating mutual benefits. Digital entrepreneurship is a format of entrepreneurship, using digital technologies and means, that transforms organizations and markets towards digital or phygital (physical and digital) action. In this thesis, we propose an innovative approach, connecting and analyzing the two phenomena through three independent studies. In study 1, a systematic literature review (SLR), we revealed the theoretical-conceptual intertwining of the two phenomena and represented this contribution in a theoretical framework with five cyclical themes: i) digital innovation in strategy and management; ii) innovation as an element to co-create value and undertake digitally; iii) information technology and collaborative digital networks; iv) co-creation of value with stakeholders; iv) performance of organizations and digital transformation. In study 2, with a survey, formulation and testing of hypotheses, modeling of structural equations based on variance and statistical regressions, we demonstrated and quantitatively measured the relationship between the phenomena, confirming the co-creation of value as a generator or promoter of digital entrepreneurship, with the employee engagement moderating this relationship. Using Necessary Conditions Analysis (NCA), we reinforce the findings, indicating that for desired levels of digital entrepreneurship it is necessary to have certain levels of value co-creation and employee engagement. In study 3, we take theory into practice in a case study on the digital transformation of a retail company, shedding new empirical light on the relationship between the phenomena. The process involved redefining strategies and the company's actions with customers and stakeholders, based on the construction of pillars of transformation: i) culture of innovation and digital culture; ii) omnichannel operations; iii) investment in IT and digital technologies; iv) business expansion and building strategic partnerships; v) administrative-financial restructuring. The thesis contributes to the literature by proving the connection (theoretical and empirical) between value co-creation and digital entrepreneurship and revisiting the dominant logic of service for the context of digitalization of companies and the market. Empirically, the work brings theory closer to the real field of organizations, collaborating with managers and suggesting strategies and actions, involved in value co-creation and digital entrepreneurship, as possibilities for greater success in digital transformation of businesses.